Conducting fieldwork on children and media: comparing research in Singapore and Vietnam. Issue 4 (2nd October 2019) - Pham, Becky; Loh, Renae Sze Ming
ABSTRACT: Reflecting on our experiences conducting fieldwork on children's media use in Singapore and Vietnam, this commentary highlights the need for researchers to develop critical understanding of different cultural and societal factors at play in diverse research environments.